ISLAMIC EDUCATIONAL LEADERSHIP IN THE DIGITAL ERA AND SOCIETY 5.0 - Hodiqotul Atfaliyah; Yosie Kristin Pandriyani; Encep Syarifudin; Eneng Muslihah; Siti Patimah (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2026)
This study aims to analyze Islamic educational leadership in the digital era and Society 5.0, which is characterized by the integration of advanced technology into various aspects of life, including education. Islamic educational leadership is required to be able to adapt to technological developments without neglecting the spiritual and moral values ??that are its main foundation. The research method used is a qualitative approach with a library research study through analysis of various relevant scientific literature. The results show that Islamic educational leadership in the digital era and Society 5.0 must be adaptive, innovative, and transformational. Educational leaders are required to be able to utilize digital technology in the learning process, institutional management, and data-based decision-making. In addition, effective leadership must also be able to integrate Islamic values ??such as amanah (trust), ihsan (good character), and uswah hasanah (good character) into daily leadership practices. Challenges faced include low digital literacy, limited resources, and resistance to change. However, there are significant opportunities available, especially in improving the quality of education through technology-based innovation. Thus, Islamic educational leadership in the digital era and Society 5.0 requires synergy between managerial competence, technological capabilities, and moral-spiritual integrity to produce a quality, adaptive, and globally competitive education system.